Pengaruh Promosi E-Katalog, Kualitas Produk, Layanan Purna Jual, Sales Representative Terhadap Kepercayaan Pelanggan Serta Dampaknya Pada Minat Beli Alat Kesehatan Pada PT. XYZ ta dampaknya terhadap Minat Beli Alat Kesehatan Pada PT.XYZ - Hilmansyah Hilmansyah; Triyono Arief Wahyudi (Research and Community Service UNIVERSITAS KALBIS, 2024)
This research analyzed the influence of E-catalogue promotion which is an e-purchasing tool provided by the government, product quality, after sales service, sales representative on customer trust and its impact on purchase intention of medical devices at PT.XYZ. This research is conducted by quantitative research method with 90 respondents divided into 3 categories, the method used is regression and correlation of each variabel with 2 sub- models using SPSS engine. The conclusion of this research result in the analysis of the first sub model, (1) Promotion of E-catalog has positive and significant impact toward customer trust, (2) product quality influences insignificantly toward customer trust,(3) after sales service influences insignificantly toward customer trust and (4) Sales Representative has a positive and significant impact toward customer trust, the conclusion of the analysis on second sub model is (5) the customer trust has positive and significantly influence the purchase intention